Population dynamics and stock assessment of two major eels (Muraenesox bagio and Congresox talabonoides) from the marine waters of Bangladesh - Barua, Suman; Liu, Qun; Alam, Mohammed Shahidul; Schneider, Petra; Mozumder, M.M.H.; Rouf, Md. Abdur (Frontiers in Marine Science, 2023)
Muraenesox bagio (black eel) and Congresox talabonoides (brown eel) are two major eels (Muraenesocidae) species which are commercially significant in the marine catch of Bangladesh, but population dynamics and stock assessment of marine eel fishery in Bangladesh are yet to be studied. This study is the first endeavour to analyze the population dynamics and stock assessment of this marine eels collected from July 2021 to May 2022 using three length-based methods namely TropFishR, the Length Based-Spawning Potential Ratio (LB-SPR) & the length-Based Indicators (LBI) and two catch-based methods including Depletion-Based Stock Reduction Analysis (DB-SRA) and the Catch-Maximum Sustainable Yield (CMSY). A slightly positive allometric growth pattern (b=3.10) for the black eel and a negative allometric growth pattern (b=2.33) for the brown eel were observed in the length-weight relationship. The parameters of von Bertalanffy Growth Function (VBGF) and the linearized length-converted catch curve (LCCC) analysis for black eel and brown eel were L∞=190.67cm and 166.63cm, k=0.18 year-1 and 0.16 year-1, and the total mortality, Z=0.70 year-1 and 0.45 year-1. The eel fishery is calculated to be overfished due to overexploitation and the stock’s spawning biomass (SPR=19% for black eel and 21% for brown eel) is close to the limit reference point but well outside the targeted range because the majority of the catches were found to have below-maturity levels. This study advised an optimum length limit to catch from 93 to 114 cm for black eel and 83 to 101 cm for brown eel. Though the estimated reference points of the CMSY were more optimistic than those from the DB-SRA, the tendency of the status of eel stock has been displayed moving towards overexploitation from a safe stock scenario. This study, therefore, recommended an annual landing limit of 250 mt as OFL (Over fishing limit) for the next ten years in association with existing management measures to maintain the present stock biomass of eel fishery over the BMSY level.